Identification of novel lncRNAs associated with sensitivity of HIV antiretroviral therapy: A two-stage matched case-control study - Minjie Chu; Yujia Chen; Gang Qin; Renfei Lu; Yuhui Yu; Zhengcheng Xu; Qiwei Ge; Zhounan Cheng; Min Li; Luyao Cao; Yuanyuan Liang; Meiyin Zou; et al. (Elsevier, 2022)
Background: To identify long non-coding RNAs (lncRNAs) that may be used as potential biomarkers of sensitivity to antiretroviral therapy (ART) against human immunodeficiency virus (HIV) infection. Method: A two-stage matched case-control study was conducted. First, in the screening stage, peripheral blood lymphocytes (PBLs) of six subjects receiving lamivudine-based ART (3 ART-resistant and 3 ART-sensitive subjects with matching durations of ART) were subjected to comprehensive microarray expression profiling in order to screen out lncRNAs associated with ART sensitivity. Secondly, during the validation stage, promising lncRNAs were evaluated via a 1:4 matched case-control study using 50 subjects (10 ART-resistant and 40 ART-sensitive subjects with matching durations of ART). Results: Seven lncRNAs were screened out (P < 1.06 × 10-3) in the first stage. Among these, two lncRNAs (n341598 and n407911) survived validation conducted at the second stage (n341598: P < 0.001; n407911: P = 0.007), while another lncRNA n406445 showed marginally significant (P = 0.049). All three showed higher expression in ART-resistant subjects compared to that in ART-sensitive subjects. The area under the ROC curve (AUC) for n341598 was 0.867 (95 % CI: 0.796-0.966; P < 0.001), which was better than that for n406445 (0.702) and n407911 (0.780). Meanwhile, the AUC for n341598 was better than that of any combination of the three lncRNAs. Conclusion: Our study identified three highly expressed lncRNAs in patients with HIV ART-resistant, among which the lncRNA n341598 may be utilized as an optimal biomarker to distinguish ART-resistant and ART-sensitive patients. Further studies aimed at revealing the molecular mechanisms underlying the regulation of ART sensitivity by n341598 are warranted to complement our findings.